Pan-Cancer Analysis Reveals CENPI as a Potential Biomarker and Therapeutic Target in Adrenocortical Carcinoma - Wu F; Li G; Shen H; Huang J; Liu Z; Zhu Y; Zhong Q; Ou R; Zhang Q; Liu S (Dove Medical Press, 2023)
Feima Wu, Guangchao Li, Huijuan Shen, Jing Huang, Zhi Liu, Yangmin Zhu, Qi Zhong, Ruiming Ou, Qing Zhang, Shuang Liu Department of Hematology, Guangdong Second Provincial General Hospital, Guangzhou, Guangdong, People's Republic of ChinaCorrespondence: Shuang Liu, Department of Hematology, Guangdong Second Provincial General Hospital, XinGangZhong Road 466#, Haizhu Distict, Guangzhou, Guangdong Province, 510317, People's Republic of China, Tel +86-20-89169214, Email liush@gd2h.org.cnBackground: Centromere protein I (CENPI) has been shown to affect the tumorigenesis of breast and colorectal cancers. However, its biological role and prognostic value in other kinds of cancer, especially adrenocortical carcinoma (ACC), remained to be further investigated.Methods: Various bioinformatics tools were adopted for exploring the significance of differential expression of CENPI in several malignant tumors from databases such as Depmap portal, GTEx, and TCGA. ACC was selected for further analyzed, and information such as clinicopathological features, the prognostic outcome of diverse subgroups, differentially expressed genes (DEGs), co-expression genes, as well as levels of tumor-infiltrating immune cells (TIIC), was extracted from multiple databases. To verify the possibility of CENPI as a therapeutic target in ACC, drug sensitivity assay and si-RNA mediate knockdown of CENPI were carried out.Results: The pan-cancer analyses showed that the CENPI mRNA expression levels differed significantly among most cancer types. Additionally, a high precision in cancer prediction and close relation with cancer survival indicated that CENPI could be a potential candidate biomarker to diagnose and predict cancer prognosis. In ACC, CENPI was closely related to multiple clinical characteristics, such as pathological stage and primary therapy outcome. High CENPI levels predicted poor overall survival (OS), progression-free interval (PFI), and disease-specific survival (DSS) of ACC patients, particularly for different clinical subgroups. Moreover, the expression of CENPI showed positive relationship to Th2 cells but negatively related to most of the TIICs. Furthermore, drug sensitivity assay showed that vorinostat inhibit CENPI expression and ACC cell growth. Additionally, si-RNA mediated knockdown of CENPI inhibited ACC cell growth and invasion and showed synergistic anti-proliferation effect with AURKB inhibitor barasertib.Conclusion: Pan-cancer analysis demonstrated that CENPI is a potential diagnostic and prognostic biomarker in various cancers as well as an anti-ACC therapeutic target.Keywords: CENPI, pan-cancer analysis, diagnosis, prognostic biomarker, adrenocortical carcinoma